Economic analysis of grid integration of variable solar and wind power with conventional power system. (15th April 2020) - Yao, Xing; Yi, Bowen; Yu, Yang; Fan, Ying; Zhu, Lei
Highlights: We investigate the integration cost of wind and solar on both the power supply and demand sides. The integration costs from both sides are increasing with the penetration of variable renewable electricity. Consumers will bear more cost of variable renewable electricity integration than power system. Solar power has a lower integration cost than wind power. Blindly reducing the renewable energy curtailment rate may not be cost-effective. Abstract: Variable renewable electricity (VRE) is expected to play an important role in global decarbonization. However, due to VRE's intermittency and uncertainty, integrating VRE into the power system may cause additional integration costs for both power systems and consumers. Estimating these integration costs can provide insights for power system planning, support policy making and power market designs. In this paper, the integration costs of wind and solar on both demand and supply sides are quantitatively investigated by an economic power dispatch model combined with Monte Carlo simulation. A case study of Guangdong Province in China is conducted under three scenarios of power mix changes (only increasing the VRE installation; replacing the existing coal-fired power; and replacing the existing coal-fired power without power storage). The results show that integration costs from both supply and demand sides are non-negligible when VRE replaces existing capacity, and the costs are increasing with the penetration rate of VRE. On supply side, it ranges from −2.3 to 12.1 /MWh for wind penetration from 5% to 30%, and −5.5 to 7.1 /MWh for that of solar penetration. Moreover, consumers on demand side will bear −7.3 to 185.9 /MWh integration costs for wind and solar integration, which is much higher than the supply side. In addition, solar power has a lower integration cost than wind power due to a more consistent power output with the load curve of power demand on the time scale. Moreover, our results reveal that blindly reducing the renewable energy curtailment rate may not be cost-effective.